1971
DOI: 10.1111/j.1476-5381.1971.tb07132.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed patterns of behaviour in morphine tolerant and abstinent rats

Abstract: Summary1. Eating, drinking and spontaneous motor activity were studied in rats receiving large daily doses of morphine. These forms of behaviour were largely suppressed when the rats were made abstinent and were restored when morphine was given again. 2. Compensation for depressions of behaviour during abstinence did not seem sufficient to account for all the stimulant effects of morphine in tolerant rats. Morphine also had slight stimulant actions in non-tolerant rats. 3. In tolerant rats, the repeated pairin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1973
1973
1986
1986

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…If this contention is valid, morphine, an opiate agonist, might facilitate feeding and water drinking in non fasted and fasted rats. Recently, many reports revealed the increments of food and water intake by morphine in non-fasted rats (8)(9)(10)(11). Grandison and Guidotti also showed that intrahypothalamic administration of ,3 endorphin, an endogeneous opiate peptide, increased food and water intake in satiated rats (12).…”
mentioning
confidence: 99%
“…If this contention is valid, morphine, an opiate agonist, might facilitate feeding and water drinking in non fasted and fasted rats. Recently, many reports revealed the increments of food and water intake by morphine in non-fasted rats (8)(9)(10)(11). Grandison and Guidotti also showed that intrahypothalamic administration of ,3 endorphin, an endogeneous opiate peptide, increased food and water intake in satiated rats (12).…”
mentioning
confidence: 99%
“…Tolerance develops to the cataleptic actions of morphine following repeated daily injections of the drug and there is a concomitant enhancement of stimulant actions on motor activity (Kumar et al, 1971;Babbini & Davis, 1972). It seems possible that, as tolerance develops, there is a further disturbance of striatal compensatory mechanisms in the lesioned rats and, as a result, bias appears in the direction of locomotor behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Although single doses of morphine result in apparently compensatory increases in the synthesis and turnover of dopamine in the striata of nontolerant rats (Clouet & Ratner, 1970;Sugrue, 1974), analogous responses to chronic morphine medication are not seen in the brains of tolerant rats Puri, Volicer & Lal, 1977). Tolerant rats, nevertheless, show marked behavioural changes for several hours after receiving their usual dose of morphine, such as increased locomotor activity and stereotyped responding (Fog, 1970;Ahyan & Randrup, 1972;Babbini & Davis, 1972), increased eating and drinking (Kumar, Mitchell & Stolerman, 1971) and reduced sexual activity (Mumford & Kumar, 1979). Aside from altered influences of other neurotransmitter systems, it has been suggested that there may be underlying and prolonged changes in the sensitivities of dopamine receptors themselves (Puri & Lal, 1973;Gianutsos, Hynes, Puri, Drawbaugh & Lal, 1974;Tarsy & Baldessarini, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the rats abruptly showed eating behavior. Kumar et al (23) reported that large doses of morphine can facilitate eating and drinking in tolerant rats. Effect of morphine injection on eating, drinking and spontaneous motor activity in morphine dependent rats produced by systemic injection (23-25) might differ from the effect in morphine dependent rats produced by a variety of techniques, including intravenous self-administration (8), the implan tation of morphine pellets and reservoir (26)(27)(28), continuous parenteral infusion (29) and oral self-administration (2-4, 30, 31).…”
Section: Discussionmentioning
confidence: 99%